Predicting microbial water quality with models: Over-arching questions for managing risk in agricultural catchments - Oliver, David M.; Porter, Kenneth D. H.; Yakov, A. Pachepsky; Muirhead, Richard W.; Reaney, Sim M.; Coffey, Rory; Kay, David; Milledge, David G.; Hong, Eunmi; Anthony, Steven G.; Page, Trevor; Bloodworth, Jack; et al. (Elsevier, 2015)
The application of models to predict concentrations of faecal indicator organisms (FIOs) in environmental systems plays an important role for guiding decision-making associated with the management of microbial water quality. In recent years there has been an increasing demand by policy-makers for models to help inform FIO dynamics in order to prioritise efforts for environmental and human-health protection. However, given the limited evidence-base on which FIO models are built relative to other agricultural pollutants (e.g. nutrients) it is imperative that the end-user expectations of FIO models are appropriately managed. In response, this commentary highlights four over-arching questions associated with: (i) model purpose; (ii) modelling approach; (iii) data availability; and (iv) model application, that must be considered as part of good practice prior to the deployment of any modelling approach to predict FIO behaviour in catchment systems. A series of short and longer-term research priorities are proposed in response to these questions in order to promote better model deployment in the field of catchment microbial dynamics.
Keywords: Catchment management; Diffuse pollution; Faecal indicator organism; Human health; Pathogens